Minimetro, Tramway or Light railway - Frederiksen, Tove (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
The background for this article is my final thesis “Minimetro, tramway or light railway”, elaborated at the Institute of Technology and Social Sciences, unit of Technology Assessment, DTU, June 1995. It is made through my surprise over the debate which arose in the press following the Ørestad Consortium’s choice of a mini-metro in preference to a tramway or a light railway as Copenh agen’s new cityline, three apparently very similar solutions but where each solution clearly had its proponents and o pponents. The debate was emotionally charged and the arguments forwarded concerned matters very di fferent to those presented by the Ørestad Consortium as being important. Following the decision in favour of the mini-metro and my own surprise concerning the links which developed among the actors’ arguments and actions, especially concerning things not mentioned in the debate, I have deconstructed the Ørestad Consortium’s choice of the mini-metro. The article, therefore, is based on the Ørestad Consortium’s own presentation of the mini-metro in preference to the other two choices, and subsequently an unravelling of the process which led to the Ørestad Consortium’s choice. This unravelling considers the participant in the debate, hereafter ’the actors’, and the choices which influenced the requirements of the mini-metro. The background for the actors’ power struggles lies in the rationalities. To unearth them would require a deeper dig. Transport- and town planning in Copenhagen express the ideologies, wishes and expect ations of future society. The rationalities are reflected in the objectives of these plans. Rationalities are the actors’ perception of problems and solutions attached to a specific distinct, in this instance transport planning in Copenhagen. Attached to a rationality is a relevant social group, which is a group of actors who have the same perception of objectives, for example with respect to transport planning, i.e. in other words a relevant social group is a group of actors who share the same rationality. The rationality, to which the actors, methods and structures (both institutions and infrastructures) are attached, is defined by the rationalities they hold. Rationalities are a part of society’s discourses 1 and elements of these discourses are made concrete in the rationality.